Dose birthweight matter to quality of life? A comparison between Japan, the U.S., and India - Chisako Yamane; Yoshirō Tsutsui (Health Economics Review, 2022)
Background: Birthweight is a widely accepted indicator of infant health and has signifcant and lasting associations. Several studies have found that low and high birthweight have signifcant negative associations with adult health. A new study in the feld of social sciences has established that birthweight has signifcant negative associations with not only adult health but also social attributes, such as income and occupation; however, no studies have evaluated the associations between birthweight and quality-of-life (QOL) attributes such as happiness. Methods: In this study, we use data from Japan, the U.S., and India, collected in 2011, in which the respondents were asked about their own birthweights to examine the long-term associations between low and high birthweight and eight outcome variables related to the QOL: adolescent academic performance, height, education, marital status, body mass index, income, health, and happiness. We regressed each of the eight outcome variables on low and high birthweight and the interaction terms of the old age and the birthweight dummies for each country. We estimated both the reduced and the recursive-structural forms. While the former estimates the total, that is, the sum of direct and indirect associations between birthweight and each outcome, the latter reports the direct association between birthweight and each outcome. Results: In Japan, while low birthweight is negatively associated with all outcomes, the associations of high birthweight were limited. In the U.S., low birthweight was not associated with any outcomes, but high birthweight had signifcantly negative associations with health and happiness. In contrast, in India, high birthweight was signifcantly and positively associated with income, health, and happiness, while low birthweight was associated with several outcomes negatively, similar to Japan. These associations were stronger in youth than in old age. Conclusion: Our study demonstrated that the associations of birthweight with QOL are widely diversifed across countries: low birthweight, rather than high birthweight, is a problem in Japan and India. However, the opposite is true for the U.S., indicating that policymakers in developed countries must pay closer attention to the problems caused by high birthweight, whereas those in developing countries are better to focus on low birthweight.
Keywords: 330; Low birthweight; Hight birthweight; Long-term associations of birthweight; Japan; the U.S.; India